1994
DOI: 10.1159/000126785
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor and Neurotensin Are Colocalized in Neurons of the Guinea Pig Ventrolateral Hypothalamus

Abstract: A double-labeling immunofiuorescence procedure was used to determine whether progesterone receptor (PR)-containing neurons in the mediobasal hypothalamus of female guinea pig also contain neurotensin (NT). Animals were ovariectomized, primed by estradiol to induce PR and injected intracere-broventricularly with colchicine to visualize NT-immunopositive neurons. Approximatively 24% of the NT-immunoreactive (IR) neurons in the ventrolateral nucleus (VL) displayed PR immunoreactivity, accounting for 4% of the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The present study shows that SOM is another neuro peptide in the VL whose synthesis may be regulated by progesterone since further immunocytochemical studies have demonstrated the presence of neurotensin [19], sub stance P [21,22] and opiates [23] in the PR-IR neurons of the guinea pig VL. At present we do not know whether these neuropeptides coexist within the same neurons con taining PR or represent separate populations.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The present study shows that SOM is another neuro peptide in the VL whose synthesis may be regulated by progesterone since further immunocytochemical studies have demonstrated the presence of neurotensin [19], sub stance P [21,22] and opiates [23] in the PR-IR neurons of the guinea pig VL. At present we do not know whether these neuropeptides coexist within the same neurons con taining PR or represent separate populations.…”
Section: Discussionsupporting
confidence: 58%
“…We found that only a very small fraction of the population of SOM-IR neurons in the Ar possess PR and that neither male nor female preoptic and hypothalamic periventricular SOM Progesterone Receptor in Hypothalamic Somatostatin Neurons neurons contain PR. As such, SOM can now be added to the list of neuropeptides found in PR-IR neurons in the VL of the guinea pig such as neurotensin [ 19] substance P [21,22] and enkephalin [23],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, neurons that putatively mediate negative feedback of progesterone on the GnRH system might be located in areas of the brain that were not investigated in this study. For instance, populations of progesterone-receptive cells have been identified in the preoptic/anterior hypothalamic area, mediobasal hypothalamus (arcuate and ventromedial nuclei) and brainstem of several species [58, 59, 60, 61, 62], including sheep [63], although their role in the regulation of GnRH secretion has not been determined. Second, a progesterone-responsive neuronal system might be activated and show increased Fos immunoreactivity some time in advance of the GnRH surge.…”
Section: Discussionmentioning
confidence: 99%
“…Receptive behavior may also be regulated by several neurotransmitter or neuromodulator systems. Because substance P (Nielsen and Blaustein, 1990; Dufourny et al, 1998), neurotensin (Warembourg and Jolivet, 1994), and somatostatin (Dufourny and Warembourg, 1996) have been shown to colocalize to different degrees with the PR in the guinea pig ventrolateral nucleus, it is conceivable that at least some of the NOS-containing neurons also contain these substances. The possible presence of NOS within these systems suggests that NO has the potential to modulate the activity of one or both of these neuronal networks and adds to our understanding of the neurochemistry of lordosis.…”
Section: Discussionmentioning
confidence: 99%